Characterization of the complete mitochondrial genome of the Atlantic seabob shrimp Xiphopenaeus kroyeri Heller, 1862 (Decapoda: Dendrobranchiata: Penaeidae), with insights into the phylogeny of Penaeidae. Issue 1 (3rd March 2022) - Cronin, Timothy J; Conrad, Isabelle; Kerkhove, Thomas R H; Hellemans, Bart; De Troch, Marleen; Volckaert, Filip A M; Baeza, J Antonio
Abstract: The Atlantic seabob shrimp, Xiphopenaeus kroyeri (Heller, 1862 ) (Penaeidae), is commonly found on western Atlantic coasts and of high commercial importance in Brazil, Suriname, and Guyana. Current genetic resources on X. kroyeri are scarce and no genomic studies are available. This study reports the complete mitochondrial genome of X. kroyeri . Using the pipeline NOVOPlasty, we assembled and circularized the complete mitochondrial genome of X. kroyeri with an average coverage of 68x per nucleotide. The AT-rich mitochondrial genome of X. kroyeri is 15, 999 bp in length and comprised of 13 protein-coding genes (PCGs), 2 ribosomal RNA genes, and 22 transfer RNA genes. A single 1, 030 bp long intergenic space is assumed to be the D-loop/Control region (CR). Selective pressure analysis indicated that the PCGs were under purifying selection. The KA /KS ratios observed for cox1, cox2, atp6, cox3, and cob were found to be much lower than the ratios observed in the other PCGs, suggesting strong purifying selection upon the former genes. The secondary structures of the tRNA genes exhibited a standard 'cloverleaf' structure, with the exception of trnS1 . A maximum likelihood phylogenetic analysis based on all PCGs indicated that X. kroyeri is more closely related to penaeids (Penaeidae) belonging to the genera Trachypenaeus Alcock, 1901, Penaeopsis Spence Bate, 1881, and Mierspenaeopsis K. Sakai & Shinomiya, 2011 . This study contributes new genomic resources for this commercially important species which may aid in distinguishing cryptic species and elucidating phylogeographic patterns.